Citra Merk, Fitur dan Kualitas Produk dalam keputusan Pembelian Smartphone Xiaomi - Nurul Ikbal Alvatwa; Muinah Fadilah; Putri Dwi Cahyani (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2021)
This study aims to determine (1) the effect of brand image on purchasing decisions for Xiaomi smartphones, (2) the effect of features on purchasing decisions for Xiaomi smartphones, (3) the effect of product quality on purchasing decisions for Xiaomi smartphones, and (4) the influence of brand image, features, and product quality on purchasing decisions for Xiaomi smartphones. This research used a quantitative approach. The population in this study were consumers who used Xiaomi smartphones. The sampling technique used purposive sampling with a sample size of 112 people. The data collection method used a questionnaire. This research uses data quality test, classical assumption test, multiple linear regression analysis and hypothesis testing. The results of this study indicate that the brand image variable has a positive and significant effect on purchasing decisions. The feature variable has no effect on purchasing decisions. Product quality variables have a positive and significant effect on purchasing decisions. The variables of brand image, features, and product quality simultaneously affect purchasing decisions.